Voluntary electronic patient record state of the art - Carneiro, Carla Margarida da Silva (2013)
Introduction: With an ongoing economic crisis, Portugal and many other countries are looking into ways to increase efficiencies in all sectors. With almost 10% of the Gross Domestic Product (GDP) spent in Healthcare, there is a need to improve the use of resources. A Voluntary Electronic Patient Record (VEPR) is an online record of health and healthcare related data provided by the patient himself, available to him, and his authorized health care providers and relatives, in a ubiquitous way anywhere/everywhere. According to some authors through VEPRs, every health institution could have an easier access to a summary of the patient’s most important health data if needed and authorized. Just like Portugal, Australia, for example, is currently preparing a health care reform and the implementation of a Personally Controlled Electronic Health Record (PCEHR) system is also being studied. Surveys to general practitioners and consumers of eHealth are being conducted in order to evaluate the quality and sustainability of Australia’s health care and to develop change and adoption strategies for the PCEHR system. VEPRs can be provided by private companies, hospitals and health organizations or health departments of governments themselves. In Portugal there is at least one VEPR free of charge provided by a private company. This has raised issues of security of data and risks, and has not been approved by the data protection agency, possibly due to considerations on its massive use as well as the ethical issues of linking it to national health data from the NHS. In addition to this private VEPR, Portugal also provides some health online services: eAgenda and eRNU (“Registo Nacional de Utentes”) since 2009. Currently, eAgenda allows patients to schedule for doctor´s appointments and to ask for prescriptions renewal. The online health service, eRNU, allows users to check their general practitioner, the health institution in which they are registered, the health services it provides and its opening schedule. VEPR can be efficient, allowing better sharing of information between health care providers through the online availability of health information. It can be convenient; provide easy access to timely and accurate information no matter where the patient is or when he needs it. It is empowering as it enables the patient to be more active and involved with his own health care. To ensure the privacy of the patient’s health information, a security program is required to allow only the appropriately authorized individuals to access the VEPR and to save the record’s data in case of a technical breakdown occurs. On the other hand, although everyone can have a VEPR, this is normally restricted to younger, more info-included citizens as access to the internet is not universal and there is a natural difficulty in older generations to use IT and Internet. This, however, can be mitigated and will only have a tendency to dissipate in future. Aims: 1. To assess the state of the art about VEPR; 2. To assess the state of the art about VEPR in Portugal; 3. To assess users expectancies towards VEPR in Portugal; 4. To help developing and set in motion a VEPR adjusted to Portuguese population’s health challenges. Methodology: This is a transversal study with a qualitative and quantitative approach. To elaborate this paper, a literature review was made in order to identify sources of information about VEPR and current state of the art on this field. It was established a cooperation with the Portuguese Ministry of Health as it was the only way to indirect and directly collect data about the portuguese VEPR, eAgenda and eRNU. A questionnaire composed of 14 questions, made anonymous, was created using Lime SurveyTM, named “Inquérito para utilizadores dos serviços eAgenda e eRNU”, permission obtained and it was then sent to eAgenda and eRNU users through their e-mail addresses. Data was processed using Microsoft Office Excel 97-2003 and statistically analyzed resorting to Epi Info 7. Because the last question was an open question, the related data was processed manually. Results: Currently, eAgenda and eRNU serve about 4% of the portuguese population. The typical user is female, married, completed high school, has children and age median 38, 5 years old. Own and household appointments scheduling were the more frequently selected as the most useful functionalities as well as those that most contributed to improvement on health care delivery. Waiting time reduction was the most frequent selected advantage of eAgenda and eRNU. Conclusions: It is to be concluded that eAgenda and eRNU are well suited for the portuguese population as only 3,28% of the inquired users pointed eAgenda and eRNU services has not having any advantage. More studies are still required to understand the patterns of use and to promote the online services so that more people, not only 4% of the overall portuguese population, may take advantage of their benefits.